1999
DOI: 10.1507/endocrj.46.209
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic versus Asymptomatic Papillary Thyroid Microcarcinoma: A Retrospective Analysis of Surgical Outcome and Prognostic Factors.

Abstract: Abstract.Although the mortality rate associated with papillary microcarcinoma

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
105
2
5

Year Published

2003
2003
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(118 citation statements)
references
References 32 publications
5
105
2
5
Order By: Relevance
“…A number of large, retrospective studies show a significant reduction in the rates of disease recurrence (61,98,99,126) and cause-specific mortality (98,99,(126)(127)(128). However, other similar studies show no such benefit, at least among the majority of patients with papillary thyroid carcinoma, who are at the lowest risk for mortality (68,101,(128)(129)(130)(131). In those studies that show benefit, the advantage appears to be restricted to patients with larger tumors (Ͼ 1.5 cm), or with residual disease after surgery, while lower risk patients do not show evidence for benefit (68,98,132).…”
Section: What Is the Role Of Postoperative Radioiodine Remnant Ablation?mentioning
confidence: 99%
“…A number of large, retrospective studies show a significant reduction in the rates of disease recurrence (61,98,99,126) and cause-specific mortality (98,99,(126)(127)(128). However, other similar studies show no such benefit, at least among the majority of patients with papillary thyroid carcinoma, who are at the lowest risk for mortality (68,101,(128)(129)(130)(131). In those studies that show benefit, the advantage appears to be restricted to patients with larger tumors (Ͼ 1.5 cm), or with residual disease after surgery, while lower risk patients do not show evidence for benefit (68,98,132).…”
Section: What Is the Role Of Postoperative Radioiodine Remnant Ablation?mentioning
confidence: 99%
“…In contrast, however, the prevalence of clinical thyroid papillary carcinoma was 1.9-11.7 per 100,000 females of all ages [3,10], which is about 1,000 times lower than that of PMC detected on ultrasonography. The marked difference between these prevalences suggests that PMC rarely grow and become clinically apparent, prompting the question of whether immediate surgery is mandatory for all PMC detected on mass screening, although PMC is also known to show multicentricity in 15-44% of lesions and regional lymph node metastasis in 14-64% of lesions [11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…8 Although its clinical significance in papillary microcarcinomas is somewhat controversial, several authors have reported that lymph node metastasis at presentation is correlated with loco-regional recurrence in papillary microcarcinomas. 5,[9][10][11] Moreover, lymph node metastasis is reported to be associated with distant metastasis of papillary microcarcinomas. [9][10][11] In the new TNM (tumor, node, metastases) staging system, lymph node metastasis is a more important factor than tumor size in overall staging.…”
mentioning
confidence: 99%
“…5,[9][10][11] Moreover, lymph node metastasis is reported to be associated with distant metastasis of papillary microcarcinomas. [9][10][11] In the new TNM (tumor, node, metastases) staging system, lymph node metastasis is a more important factor than tumor size in overall staging. 12 Overexpression of cyclin D1, 13 S100A4 14 and MUC1, 15 loss of p27 13,16 and presence of the BRAF mutation 17,18 have been suggested as important predictive factors for relapse or nodal metastasis of papillary thyroid carcinoma.…”
mentioning
confidence: 99%